Promoção da saúde auditiva: contribuições da prática educativa para os trabalhadores de uma lavanderia hospitalar - Fontoura, Francisca Pinheiro (2016)
Due to their environmental conditions, hospital laundries as a workplace are a serious problem. These conditions pose health and safety hazards to workers and, consequently, favor the occurrence of accidents as well as the development of occupational illnesses, such as hearing pathologies. These adversities are attributed to the fact that workers operate machines which produce noise above the tolerance limit established by law on a daily and continuous base. As a result, their quality of life is affected, which requires actions to promote knowledge and learning of workers’ hearing healthcare-related issues in those workplaces. In this perspective, an evaluative, quantitative research study was carried out, which objectified to analyze the contributions of the educational practice to promote workers’ hearing health of a hospital laundry belonging at a Federal Public Teaching Hospital located in the city of Curitiba - Paraná State, Brazil. The studied population comprised a total of 80 workers subdivided in: Intervention Group (n=20) and Non-Intervention Group (n=60). The procedures used were: Identification of Educational Diagnosis; Planning and Structuring of the Educational Group Interventions (Action Plan); Development of the Educational Group Interventions (Implementation of the Action Plan), and Effectiveness Assessment of the Educational Group Interventions. In order to identify laundry workers’ educational diagnosis, a data collection instrument (Version A) was used, which encompassed personal identification data and consisted of 36 questions. Questions numbers 1 to 22 were adapted from the questionnaire called “Beliefs and Attitudes about Hearing Loss and Protection”, developed and validated by the National Institute for Occupational Safety and Health, which addresses this theme; the others are correlated questions with it, such as: Harmful hearing habits; Noise effects on health and hearing; Knowledge and guidance on hearing health, and questions on the Training of the Hearing Conservation Program. The theoretical approach underpinning planning and structuring of the educational group interventions was the Problem-solving and Participatory Methodology. Programming was defined after the educational diagnosis. In order to assess the impact of the educational intervention and the activities carried out in the interventions, the instruments used were as follows: “Beliefs and Attitudes about Hearing Loss and Protection” questionnaire, Version B, and an assessment form developed by the researcher. After the educational intervention, both Groups had to answer the Version B of the questionnaire; a total of 80 questionnaires were validated for analysis. Results found in the pre-intervention phase showed that both groups featured scarce knowledge on hearing health in the work setting. However, after the educational intervention, there was significant knowledge improvement towards hearing health at work in the Intervention Group, which showed an increase in the correct answers for the assessed questions to 72.22% in the post-intervention (Questionnaire B) phase from 27.78% in the pre-intervention (Questionnaire A) phase. In the Non-Intervention Group, the average percentage of correct answers for the assessed questions was 16.67% in the questionnaire A and, in the questionnaire B, was 19.44%. It can be concluded that the educational proposal grounded in the problem-solving and participatory methodology proved to be a major strategy in the workers’ involvement with the theme addressed in the group interventions and, consequently, it expanded the knowledge on hearing health in the work setting among the participants of the Intervention Group.